CYP3A genetic variation and taxane-induced peripheral neuropathy: a systematic review, meta-analysis, and candidate gene study - McEvoy, Laurence; Cliff, Joanne; Carr, Daniel F; Jorgensen, Andrea; Lord, Rosemary; Pirmohamed, Munir (Frontiers in Pharmacology, 2023)
Background: Taxane-induced peripheral neuropathy (TIPN) is an important cause of premature treatment cessation and dose-limitation in cancer therapy. It also reduces quality of life and survivorship in affected patients. Genetic polymorphisms in the CYP3A family have been investigated but the findings have been inconsistent and contradictory. Methods: A systematic review identified 12 pharmacogenetic studies investigating genetic variation in CYP3A4*22 and CYP3A5*3 and TIPN. In our candidate gene study, 288 eligible participants (211 taxane participants receiving docetaxel or paclitaxel, and 77 control participants receiving oxaliplatin) were successfully genotyped for CYP3A4*22 and CYP3A5*3. Genotyping data was transformed into a combined CYP3A metaboliser phenotype: Poor metabolisers, intermediate metabolisers and extensive metabolisers. Individual genotypes and combined CYP3A metaboliser phenotypes were assessed in relation to neurotoxicity, including by meta-analysis where possible. Results: In the systematic review, no significant association was found between CYP3A5*3 and TIPN in seven studies, with one study reporting a protective association. For CYP3A4*22, one study has reported an association with TIPN, while four other studies failed to show an association. Evaluation of our patient cohort showed that paclitaxel was found to be more neurotoxic than docetaxel (p < 0.001). Diabetes was also significantly associated with the development of TIPN. The candidate gene analysis showed no significant association between either SNP (CYP3A5*3 and CYP3A4*22) and the development of TIPN overall, or severe TIPN. Meta-analysis showed no association between these two variants and TIPN. Transformed into combined CYP3A metaboliser phenotypes, 30 taxane recipients were poor metabolisers, 159 were intermediate metabolisers, and 22 were extensive metabolisers. No significant association was observed between metaboliser status and case-control status. Summary: We have shown that the risk of peripheral neuropathy during taxane chemotherapy is greater in patients who have diabetes. CYP3A genotype or phenotype was not identified as a risk factor in either the candidate gene analysis or the systematic review/meta-analysis, although we cannot exclude the possibility of a minor contribution, which would require a larger sample size.